The risk of indoor sports and culture events for the transmission of COVID-19 (Restart-19) - Moritz, S.; Gottschick, C.; Horn, J.; Popp, M.; Langer, S.; Klee, B.; Purschke, O.; Gekle, M.; Ihling, A.; Mikolajczyk, R. (Nature Communications, 2021)
Nearly all mass gathering events (MGEs) worldwide have been banned since the outbreak of SARS-CoV-2 as they are supposed to pose a considerable risk for transmission of COVID-19. We investigated transmission risk of SARS-CoV-2 by droplets and aerosols during an experimental indoor MGE (using N95 masks and contact tracing devices) and conducted a simulation study to estimate the resulting burden of disease under conditions of controlled epidemics. The number of exposed contacts was <10 for scenarios with hygiene concept and good ventilation, but substantially higher otherwise. Of subsequent cases, 0%-23% were attributable to MGEs. Overall, the expected additional effect of indoor MGEs on burden of infections is low if hygiene concepts are applied and adequate ventilation exists.